KAJIAN PREFERENSI KONSUMEN IKAN LELE - Ngadiyo Ngadiyo; Sitti Aida Adha Taridala; Yusnaini Yusnaini (Jurnal Sosio Agribisnis, 2017)
Consumers’preference can be determined through consumers’ level of preference to the products of catfish pecel. The preference describes the attributes of catfish pecel produced by the sellers and accepted by the consumers. The purposes of this study were: to analyze factors that consumers take into account when buying catfish; to measure consumers’ attitude and behaviors towards the products of catfish. Conducted in Kendari, Southeast Sulawesi, employed a Multiattribut Fishbone Attitude Analysis and Konjoin Analysis to measure consumers’ attitute and behaviors towards catfish pecel. The results of Multiattribute Fishbein Attitude Analysis showed that the consumers’ attitudes towards catfish pecel was 65,77 percent. This indicated that the consumers’ attitude was “good enough”, with 65,77 percent being higher that the expected 32,568 or 100 percent.  In other words, the consumers were satisfied and responded to the product positively, and it is therefore probable that they will consume the same product again, notwithstanding catfish pecel.  The results of Konjoin analysis showed that in terms of preference, the consumers’ of catfish pecel in Kendari are in favor of catfish with a measurement of 9-10 fish per kilogram, brownish black, medium taste, cheap, clean, and soft in texture.Keywords: catfish, catfish pecel, Fishbein, Conjoint